Nanomanufacturing of RGO‐CNT Hybrid Film for Flexible Aqueous Al‐Ion Batteries. Issue 37 (14th August 2020) - Liu, Siliang; Wang, Panpan; Liu, Chang; Deng, Yida; Dou, Shuming; Liu, Yingjun; Xu, Jie; Wang, Yilin; Liu, Weidi; Hu, Wenbin; Huang, Yan; Chen, Yanan
Abstract: A highly electrically conductive film‐type current collector is an essential part of batteries. Apart from the metal‐based current collectors, lightweight and highly conductive carbon materials such as reduced graphene oxide (RGO) and carbon nanotubes (CNTs) show great potential as current collectors. However, traditional RGO manufacturing usually requires a long time and high energy, which decreases the product yielding rate and manufacturing efficiency. Moreover, the performance of the manufactured RGO needs to be further improved. In this work, CNT and GO are evenly mixed into GO‐CNT, which can be directly reduced into RGO‐CNT by Joule heating at 2936 K within less than 1 min. The fabricated RGO‐CNT achieves a high electrical conductivity of 2750 S cm −1, and realizes a 10 6 ‐fold increase. The assembled flexible aqueous Al‐ion battery with RGO‐CNT as the current collector exhibits impressive electrochemical performance in terms of superior cycling stability and exceptional rate capability, and excellent mechanical ability regarding the tolerance to mechanical damage such as bending, folding, piercing, and cutting without detrimental consequences. Abstract : In this work, carbon nanotubes (CNTs) and graphene oxide GO are evenly mixed into GO‐CNT, and directly reduced into reduced GO (RGO)‐CNT by Joule heating, which enhances the product yielding rate and manufacturing efficiency. The fabricated GO‐CNT achieves a high electrical conductivity. The assembled flexible aqueous Al‐ion battery with RGO‐CNT as the current collector exhibits impressive electrochemical performance.